2018
DOI: 10.1001/jama.2018.8405
|View full text |Cite
|
Sign up to set email alerts
|

Direct Primary Care

Abstract: Primary care is the bedrock of reform of the US health system. New payment and care delivery models emphasize the importance of primary care medical homes with reimbursement prioritizing value over volume. It remains unclear how best to restructure US health care spending to attain the Triple Aim (ie, improving the experience of care, improving the health of populations, and reducing per capita costs of health care) as well as the 4 C's of primary care (contact, continuity, comprehensiveness, and coordination)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The present study observed several references regarding favorable communication with the office and physician. Beyond the conventional office visit, DPC physicians may offer increased physician accessibility through electronic correspondence with patients and home visits which are not traditionally offered by FFS models (19). DPC also promises more flexible appointment scheduling as demonstrated by a participant who reportedly switched to DPC after experiencing difficulties with scheduling in the FFS model.…”
Section: Discussionmentioning
confidence: 99%
“…The present study observed several references regarding favorable communication with the office and physician. Beyond the conventional office visit, DPC physicians may offer increased physician accessibility through electronic correspondence with patients and home visits which are not traditionally offered by FFS models (19). DPC also promises more flexible appointment scheduling as demonstrated by a participant who reportedly switched to DPC after experiencing difficulties with scheduling in the FFS model.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor Dr Adashi and colleagues stated that DPC enhances primary care–patient relationships and improves care coordination efforts while causing steep cost-sharing burdens, circumvention of quality metrics and incentive structures, increased primary care physician need, and exacerbation of disparities in primary care coverage. I have observed other benefits and question these drawbacks.…”
mentioning
confidence: 99%
“…To the Editor The Viewpoint by Dr Adashi and colleagues raised several criticisms of direct primary care (DPC) that ignored the context in which DPC has emerged. Direct primary care has evolved in affirmation of the primacy of the patient-physician therapeutic relationship and rejection of bureaucratic and economic burdens on clinicians.…”
mentioning
confidence: 99%
“…The claim that DPC “lacks the necessary oversight needed to hold physicians accountable for data reporting as well as individual and population health outcomes” is at odds with the central tenet of the clinician’s fiduciary responsibility—to place the patient’s interests above others, including data reporting and population health outcomes.…”
mentioning
confidence: 99%